Pengaruh Environmental Performance dan Capital Structure terhadap Kinerja Keuangan pada Perusahaan Sektor Basic Materials Periode 2021-2024 - Arlin Choirun Nisa; Acynthia Ayu Wilasittha (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2026)
This research examines the relationship between environmental performance, capital structure, and the financial performance of basic materials companies listed on the Indonesia Stock Exchange during 2021–2024. A quantitative approach was employed using panel data regression analysis. The sample consisted of 32 companies selected through purposive sampling, resulting in 128 firm-year observations. Data processing was conducted in Stata 17, and the Random Effect Model (REM) was determined to be the most suitable estimation model. Financial performance was proxied by Return on Assets (ROA), environmental performance was evaluated using PROPER ratings, and capital structure was measured through the Debt-to-Equity Ratio (DER). In addition, firm size and sales growth were incorporated as control variables. The findings reveal that environmental performance does not show a significant effect on financial performance, indicating that environmental initiatives have not yet generated direct financial benefits for firms. Conversely, capital structure negatively and significantly influences financial performance, suggesting that higher debt utilization may reduce company profitability. Furthermore, the simultaneous analysis indicates that environmental performance, capital structure, firm size, and sales growth jointly affect financial performance. This study enriches the literature on corporate financial performance by providing empirical evidence from Indonesian basic materials companies. Overall, the results indicate that short-term financial performance is more strongly associated with internal financial management, particularly capital structure policies, than with environmental performance practices